THE INFLUENCE OF ORGANIZATIONAL CITIZENSHIP BEHAVIOR AND JOB SATISFACTION ON THE PERFORMANCE OF EMPLOYEES OF BIRO HUKUM SEKRETARIAT DAERAH PROVINSI SULAWESI SELATAN - Windi Dwi Astuti; Burhanuddin, Chalid Imran Musa, M. Ikhwan Maulana Haeruddin, Nurul Fadilah Aswar (Jurnal Ekonomi dan Bisnis, 2025)
This study aims to analyze the effect of organizational citizenship behavior and job satisfaction on the performance of employees of the Legal Bureau of the Regional Secretariat of South Sulawesi Province. This research uses quantitative methods with descriptive approaches and multiple linear regression analysis. The sampling technique used saturated samples with 66 employees as respondents. The data obtained were analyzed using the t test, f test and determination coefficient test to test the effect of organizational citizenship behavior variables and job satisfaction on employee performance. The results showed that organizational citizenship behavior and job satisfaction had a positive and significant effect on employee performance both partially and simultaneously. The significance value for organizational citizenship behavior is 0.019 and the t- count value is 2.403 greater than the t-table and the significance value of job satisfaction is 0.017 and the t-count value is 2.454 greater than the t-table, which shows a positive and significant effect. Simultaneously, organizational citizenship behavior and job satisfaction contribute greatly to employee performance. This research suggests that organizations should be more proactive in encouraging organizational citizenship behavior or employee voluntary behavior and increasing employee job satisfaction through managing a conducive work environment, appreciation and improving work facilities so as to create optimal and sustainable employee performance.